2006
DOI: 10.2334/josnusd.48.93
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies for assessment of apical and coronal leakage of endodontic filling materials: a critical review

Abstract: Keywords: dye dilution technique; dyes; filtration. IntroductionMicroorganisms present inside root canals may remain active in the dentinal tubules even after vigorous chemicalmechanical preparation. Thus, perfect apical sealing is desirable to prevent the remaining bacteria and their endotoxins from reaching the root apex (1,2). Apical leakage is considered to be a common cause for endodontic therapy failure, and is influenced by many variables such as different filling techniques, the physical and chemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
122
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 41 publications
(72 reference statements)
1
122
0
5
Order By: Relevance
“…Among them linear measurement of tracer dye penetration technique is most frequently used. 15 In this study we compare, in vitro, sealing ability of four different root canal sealers; Acroseal (Septodont, Saint-Maur, France), AH Plus (Dentsply De Trey.GmbH, Konstanz, Germany), Endoflas-FS (Sanlor and CIA S. en C.S. Cali Colombia) and Endomethasone N (Septodont, Saint Maur, France) by the measurement of linear dye penetration using stereomicroscope (Olympus, USA).…”
Section: Introductionmentioning
confidence: 99%
“…Among them linear measurement of tracer dye penetration technique is most frequently used. 15 In this study we compare, in vitro, sealing ability of four different root canal sealers; Acroseal (Septodont, Saint-Maur, France), AH Plus (Dentsply De Trey.GmbH, Konstanz, Germany), Endoflas-FS (Sanlor and CIA S. en C.S. Cali Colombia) and Endomethasone N (Septodont, Saint Maur, France) by the measurement of linear dye penetration using stereomicroscope (Olympus, USA).…”
Section: Introductionmentioning
confidence: 99%
“…The failure of various sealers may be due to their chemical composition and physical properties (such as adhesiveness, dimensional stability, flow, solubility). 8 Generally, groups of AH26 sealer showed significantly less coronal leakage in comparison to groups of ZOE sealer especially Discussion when canals obturated by obtura II although the result was non significant in group obturated by cold lateral compaction but gives better sealing. This result some what in agreement with some author's studies [18][19][20] as they showed that the epoxy resin sealer had better sealing ability than ZOE sealer and the most efficient adhesion between sealer and root canal walls achieved when epoxy resin sealer was used.…”
Section: Stereomicroscopic Evaluationmentioning
confidence: 97%
“…15 Many in vitro methods have been used to evaluate the sealing qualities of endodontic filling materials, but most studies have used methylene blue dye because it is inexpensive, easy to manipulate, has a high degree of staining, very small molecular weight even lower than that of bacterial toxins, the same leakage as butyric acid and shows a deeper penetration than other dyes therefore was used in this study. 5,8,16 Air entrapped within the root canal filling material or inside the root canal system may inhibit penetration of dye into the pores and gaps. Oliver and Abbott stated that after centrifugation at 3,000 rpm for 5 minutes, dye penetration was 91.7%; dye penetration by passive immersion was 20.7%.…”
Section: Stereomicroscopic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different methods for evaluating endodontic materials microleakage such as bacteria leakage, dye or ink, radio isotopes, electrochemical and fluid filtration techniques (6). However, it seems to be that dye penetration is the easiest and most popular method (1, 6).…”
Section: Introductionmentioning
confidence: 99%